2004
DOI: 10.1200/jco.2004.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Childhood Acute Promyelocytic Leukemia With All-Trans-Retinoic Acid and Chemotherapy

Abstract: ATRA combined with CT for induction and also probably for maintenance provides as favorable results in children with APL as in adults and currently constitutes the reference first-line treatment in both age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
127
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 37 publications
11
127
1
3
Order By: Relevance
“…[1][2][3][4][5][6] In children, we recently showed that, with ATRA and combination chemotherapy, the outcome of APL was similar to that of adult APL. 7 The incidence of patients aged more than 60 and 70 years ranged from 15-20 and 1-6%, respectively, in published APL series. [2][3][4][5][6] To our knowledge, two studies have specifically analyzed the impact of ATRA on the outcome of elderly APL patients.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In children, we recently showed that, with ATRA and combination chemotherapy, the outcome of APL was similar to that of adult APL. 7 The incidence of patients aged more than 60 and 70 years ranged from 15-20 and 1-6%, respectively, in published APL series. [2][3][4][5][6] To our knowledge, two studies have specifically analyzed the impact of ATRA on the outcome of elderly APL patients.…”
Section: Introductionmentioning
confidence: 99%
“…PTC secondary to ATRA administration for APL has been well described in the literature through case reports in both the pediatric and young adult populations [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and, among adults, has been most often associated with obese women of childbearing age [34]. However, all patients described in this report were males with a wide age range and body mass indexes (BMIs) consistent with an overweight (BMI 25.0-29.9 kg/m 2 ) or obese (BMI Z30 kg/m 2 ) stature.…”
Section: Discussionmentioning
confidence: 99%
“…PTC following ATRA administration for APL has been well described [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. However, reports of PTC resulting specifically from dual differentiation therapy are currently lacking, and there is a paucity of evidence describing management of this condition specifically in patients with APL, where continuation of therapy is necessary for optimal clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that t(15;17) is not detected by conventional cytogenetic analysis in 10% of APL cases; however, the majority of cases showing morphological APL, but lacking t(15;17), remain associated with the formation of the PML/RARα fusion gene (Stone and Mayer, 1990;Hiorns et al, 1994;Zaccaria et al, 2002;Oh et al, 2003;de Botton et al, 2004;Owatari et al, 2007). The main reason is either the presence of cryptic insertion events or complex rearrangements leading to PML/RARα fusion (Hiorns et al, 1994).…”
Section: Discussionmentioning
confidence: 99%